What do young adults know about palliative care? A cross-sectional survey. (February 2021) - Mallon, A.; Slater, P.; Hasson, F.; Casson, K.; McIlfatrick, S.
Abstract: Objectives: A public health approach to palliative care that reorientates care towards the public is advocated in global policy. The public are drivers in identifying care priorities and partners in finding solutions to care issues; however, a necessary prerequisite is that the public knows what palliative care is and what it can achieve. The aim of this study was to investigate what young adults, an important cohort of the public, know about palliative care and identify key predictors of knowledge. Study design: This is a cross-sectional online survey. Methods: A cross-sectional online survey measured knowledge of palliative care using the Palliative Care Knowledge Scale (PaCKS), with young adults (aged 18–29 years) recruited from a university in the UK. Data relating to demographic characteristics and familiarity and experience of palliative care were collected, with descriptive, bivariate and multivariate analyses undertaken to determine respondents' knowledge levels and key predictors. Results: In total, 83% (n = 710) of respondents (n = 859) had heard of the term palliative care. The mean score on the PaCKS was 8.87 (standard deviation = 3.4, range = 0–13); men had lower levels of knowledge ( P = 0.016). Most respondents were aware that palliative care is not specifically for those with cancer or exclusively for older populations. They were unsure of timing and other key aspects reporting significant levels of 'I don't 'know' responses. Linear regression analysis demonstrated that familiarity and experience of palliative care moderated demographic influences (age, gender, education level) on knowledge (β = 0.45, P < 0.001). Conclusions: The findings suggest that despite high levels of awareness and familiarity with the term, significant numbers of respondents indicated a lack of knowledge of palliative care rather than inaccurate knowledge. This suggests the need for public health organisations to partner with palliative care sectors to develop and disseminate clear unequivocal messaging relating to the breadth of palliative care that both informs and engages young adults. Highlights: The majority of respondents had heard of the term palliative care. Familiarity and experience of palliative care strongly predicted knowledge scores. Significant 'I don't 'know' responses suggest knowledge deficits not misinformation. Public health initiatives should both engage and inform this young population.